Heart failure with improved ejection fraction: patient characteristics, clinical outcomes and predictors for improvement - Segev, Amitai; Avrahamy, Benny; Fardman, Alexander; Matetzky, Shlomi; Freimark, Dov; Regev, Ohad; Kuperstein, Rafael; Grupper, Avishay (Frontiers in Cardiovascular Medicine, 2024)
Background Heart failure with improved ejection fraction (HFimpEF) is a recently recognized entity presenting a diagnostic and therapeutic challenge. Our aim was to characterize the profile of HFimpEF patients and evaluate predictors for EF lack of improvement among heart failure with reduced ejection fraction (HFrEF) patients. Methods We included ambulatory HFrEF patients (EF≤40%) between January 1, 2015, and September 1, 2022, with two consecutive echocardiography exams at least 6 months apart. HFimpEF was defined as improved EF from ≤40%–>40% and by ≥10%. Results A total of 567 HFrEF patients (72% male, 54.3 ± 14.4 years old) were analyzed. Patients without EF improvement were more likely to be male, had more comorbidities, ischemic cardiomyopathy (ICMP), markers of adverse cardiac remodeling (lower EF and higher left and right ventricular diameters) and presence of late gadolinium enhancement (LGE) in MRI (P < 0.05 for all). In a multivariate analysis, male sex, ICMP, lower EF, larger ventricular size and LGE remained independent predictors for lack of EF improvement. A prediction model for lack of EF improvement including LVEF, LV diameter, diastolic blood pressure and ischemic etiology exhibited an area under the ROC curve of 0.77 (95% CI 0.73–0.81; P < 0.001). HFimpEF patients had better prognosis with lower hospitalizations and mortality rates. Guideline directed medical therapy (GDMT) were associated with improved outcomes in both groups regardless of EF improvement. Conclusions Lack of improvement in EF among HFrEF patients may be predicted by HF etiology and imaging parameters of adverse cardiac remodeling, and is associated with worse prognosis. GDMT were associated with improved outcomes in both HFimpEF and HFrEF patients.